Pengaruh EPS, ROE, Risiko Sistematis terhadap Return Saham Perusahaan Otomotif di BEI - Kusuma Pinatih, Luh Putu Widiantari; Lestari, Putu Vivi (E-Jurnal Manajemen, 2014)
High rate of return would be expected by each investor in invested funds. The financial information used by investors to assess the company's financial performance. The purpose of study was to determine the effects of EPS, ROE, and systematic risk either simultaneously or partially on stock returns automotive companies in the Stock Exchange in 2010-2012. The technique used is the determination of sample non probabability sampling, ie sampling saturated by 12 companies. The results of research by multiple linear regression analysis showed that simultaneous EPS, ROE, systematic risk significant effects on stock returns and partially EPS, ROE, systematic risk significant positive effects on stock returns. Keywords : EPS, ROE, systematic risk, stock returns
Keywords: EPS, ROE, systematic risk, stock returns